Effects of Two Teaching Strategies on Preschoolers’ Oral Language Skills: Repeated Read-Aloud With Question and Answer Teaching Embedded and Repeated Read-Aloud With Executive Function Activities Embedded - Chien, Hsin Ying (Frontiers in Psychology, 2020)
The purpose of this study was to investigate the impact of two teaching strategies on preschoolers’ oral language skills: repeated read-aloud with question and answer teaching embedded, and repeated read-aloud with executive function activities embedded. A quasi-experimental pretest–posttest design was employed. Children ranging in age from 4 years 6 months to 6 years and 4 months participated in the study (n = 53). They were recruited from preschools in Taitung, Taiwan, randomly assigned to the three study groups. 36 children were divided and assigned to the two experimental groups (question and answer teaching group and executive function group), while the remaining 17, to the control group. The participating preservice teachers attended 32 hours of training which included the theory, practice, and outcome evaluation measure for the teaching strategies implemented. The intervention spanned two months. Oral language tests (curriculum-based receptive vocabulary, inferential comprehension, and oral comprehension) were administered before and after the intervention. The findings revealed that both experimental groups positively impacted participants' receptive vocabulary and oral comprehension when compared with the control group, although the performances between the two experimental groups did not differ significantly. For inferential comprehension, there was no statistically significant difference across the three groups. Implications of the study findings are discussed and potential topics for future research proposed.